Monoclonal antibodies against lipopolysaccharide protect against Pseudomonas aeruginosa challenge in mice - Kang, Jason; Mateu-Borrás, Margalida; Monroe, Hunter L.; Sen-Kilic, Emel; Miller, Sarah Jo; Dublin, Spencer R.; Huckaby, Annalisa B.; Yang, Evita; Pyles, Gage M.; Nunley, Mason A.; Chapman, Josh A.; Amin, Md Shahrier; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa is a common cause of hospital-acquired infections, including central line-associated bloodstream infections and ventilator-associated pneumonia. Unfortunately, effective control of these infections can be difficult, in part due to the prevalence of multi-drug resistant strains of P. aeruginosa. There remains a need for novel therapeutic interventions against P. aeruginosa, and the use of monoclonal antibodies (mAb) is a promising alternative strategy to current standard of care treatments such as antibiotics. To develop mAbs against P. aeruginosa, we utilized ammonium metavanadate, which induces cell envelope stress responses and upregulates polysaccharide expression. Mice were immunized with P. aeruginosa grown with ammonium metavanadate and we developed two IgG2b mAbs, WVDC-0357 and WVDC-0496, directed against the O-antigen lipopolysaccharide of P. aeruginosa. Functional assays revealed that WVDC-0357 and WVDC-0496 directly reduced the viability of P. aeruginosa and mediated bacterial agglutination. In a lethal sepsis model of infection, prophylactic treatment of mice with WVDC-0357 and WVDC-0496 at doses as low as 15 mg/kg conferred 100% survival against challenge. In both sepsis and acute pneumonia models of infection, treatment with WVDC-0357 and WVDC-0496 significantly reduced bacterial burden and inflammatory cytokine production post-challenge. Furthermore, histopathological examination of the lungs revealed that WVDC-0357 and WVDC-0496 reduced inflammatory cell infiltration. Overall, our results indicate that mAbs directed against lipopolysaccharide are a promising therapy for the treatment and prevention of P. aeruginosa infections.